Are the effects of monetary policy in the euro area greater in recessions than in booms? - Gert Peersman; Frank Smets (European Central Bank (ECB), 2001)
This paper investigates whether monetary policy impulses have asymmetric effects on output growth in seven countries of the euro area (Germany, France, Italy, Spain, Austria, Belgium and the Netherlands). First, it is shown that these seven countries share the same business cycle. Next, strong evidence is presented that area-wide monetary policy impulses, measured as the contribution of monetary policy shocks to the short-term interest rate in a simple VAR for the euro area economy, have significantly larger effects on output growth in recessions than in booms. These differences are most pronounced in Germany, France, Italy, Spain, and Belgium, while they are much smaller in Austria and the Netherlands
Keywords: E4; E5; 330; monetary policy